Trends in Latin American forestry decentralisations: legal frameworks, municipal governments and forest dependent groups - Larson, A.M.; Pacheco, P.; Toni, F.; Vallejo, M. (2007)
How are forestry decentralisations evolving in Latin America? What role are municipal governments playing, and to what extent are the needs of forest-dependent peoples being taken into account? This article represents a synthesis of research findings from Bolivia, Brazil, Guatemala, Honduras and Nicaragua. It assesses current trends in Latin American forestry decentralisations, with particular attention to different conceptions of decentralisation, the role of sub-national governments and the problems of forest-dependent groups. With regard to sub-national governments, the research finds that the principal tendency in the decentralisation of decision-making over forests is through contractual arrangements between local or state governments and forestry institutes. For their part, forest-dependent groups are not able to improve their opportunity to engage in forestry-based activities without specific policies operating in their favour – beginning with secure access to forest resources – and such policy changes have most often come about in response to organised demands and in policy spheres outside of forestry.